Formation of nickel–iron meteorites by chemical fluid transport - Werner Schrön (ScienceOpen Research, 2017)
The deposition of solid material from the gas phase via chemical vapor transport (CVT) is a well-known process of industrial and geochemical relevance. There is strong evidence that this type of thermodynamically driven chemical transport reaction plays a significant role in certain natural processes. This article presents detailed evidence that CVT is a highly plausible mechanism for the formation of iron meteorites. In this study, naturally occurring CVT is referred to as “chemical fluid transport” (CFT) and the end products deposited from the gas phase as “fluidites.” Treating iron meteorites as cosmic fluidites enables simple solutions to be found to the problem of how they formed and to numerous related and in some cases unresolved questions. This study is based on a thermodynamic trend analysis of solid–gas equilibrium reactions involving chlorine- and fluorine-containing compounds of 42 chemical elements that include a systematic examination of reaction dominance switching behavior. In order to assess the transport behavior of the individual elements, the reaction-conditioned pressures p MeX were calculated from the equilibrium constants. For a selected group of minerals, the relative propensity of these minerals to deposit from the gas phase was then derived from the equilibrium constants. The study shows that octahedrites, hexahedrites and ataxites formed as a result of the transport of metal chlorides and fluorides (CFT) during accretion within the solar nebula. Siderophile elements are characterized by the similarities in their chemical transport properties. These chemical properties of the elements, expressed in the form of the reaction-conditioned pressure, play a key role in determining the chemical composition of iron meteorites. The mobilization process that leads to the formation of the gaseous metal halides MeX includes the reduction of oxides. The deposition of nickel–iron bodies occurs via back reaction after the transport of the gaseous halides. The back reaction leads to the thermodynamically favored deposition of schreibersite before troilite and of troilite before kamacite/taenite. The deposition temperature of octahedrites and hexahedrites lies below the temperature at which Widmanstätten patterns would be destroyed, while that of ataxites lies slightly above. Similarly, the occurrence of thermally instable cohenite in meteorites provides further support for the fluidite character of irons. The variation in the trace element concentrations in iron meteorites is explained by enrichment and depletion mechanisms in the gas phase. The striking correlation between gallium and germanium abundances in iron meteorites is the result of similarities regarding the mobilization phase and the reaction dominance switching behavior of both elements, and crystal isomorphism. These findings are supported by numerous arguments that provide evidence for the CFT model. The occurrence of the mineral lawrencite FeCl 2 in meteorites is interpreted as an indication of the effectiveness of the chemical transport of FeCl 2 . The presence of meteorite alteration and the observed deviations from the solar elemental abundances in silicate meteorites are also explained in terms of the effectiveness of CFT-based mobilization.